ASCIA guidelines for prevention of anaphylaxis in schools, pre‐schools and childcare: 2012 update. Issue 5 (6th May 2013) - Vale, Sandra; Smith, Jill; Said, Maria; Dunne, Geraldine; Mullins, Raymond; Loh, Richard
Abstract Appropriate management and prevention of anaphylaxis in the school, pre‐school and childcare settings requires advanced planning and communication. The Australasian Society of Clinical Immunology and Allergy has developed Guidelines for Prevention of Anaphylaxis in Schools, Pre‐schools and Childcare to assist school, pre‐school and childcare staff in appropriate implementation of risk‐minimisation strategies. Risk‐minimisation strategies recommended take into consideration the needs of the allergic child; effectiveness of measures; stresses on parents and staff, the allergic child and their peers; and the implications of the recommended risk‐minimisation strategies. These Guidelines address risk‐minimisation strategies for food, insect and medication allergies; however, the majority of strategies relate to food allergy due to the higher risk of exposure in these settings. Training in recognition of allergic symptoms (including anaphylaxis), appropriate response and treatment, as well as how to prevent exposure to known allergens are essential for effective anaphylaxis management in the school, pre‐school and childcare settings.